ROLE PLAYING UNTUK MENINGKATKAN KECERDASAN EMOSI SISWA SMP - Paninggar, Dhea Ajeng Gading; Djannah, Wardatul; Hidayat, Sri Wiyanti (Universitas Sebelas Maret, 2014)
This research was Quasi Experimental Design. The subject of this research werethe students of eighth grade of Junior High School who have low emotional intelligence. Those subject got by the value of Q1 and divided into two groups, control group and experiment group which each group composed of 31 students which choosen proportinately according to pretest score. The result of the research show the result of T-count 3,141 with p vale 0,03. So, it can be concluded that there were significant difference between experiment group that accept role playing treatment, with control group that don?t accept role playing treatment.